(untitled) (Training and Practice : Journal of Educational Sciences, 2020)
My study is about a pedagogical innovation which seems to be quite strange and divisive at first hearing: a nocturnal kindergarten. Several questions may arise when using these two words together. Kindergarten? At night? What purpose does it serve? Is there need for this? In my research, we can also get answers to these questions. Using a questionnaire, I examined these issues with two target groups, parents and kindergarten teachers. The topic, as I predicted, was completely divisive, opposing views were expressed, the analysis of which was very interesting. It is puzzling how differently the topic was approached. What can be said for sure is that this pedagogical innovation will also have a long way to go to be possibly accepted widely in the future.